Correlation Between Sleep Duration and Visual Acuity: A Single Center Study - Arianto, Huda Fajar; Pasaribu, Irma Andriani; Artati, Indira Retno (Universitas Airlangga, 2023)
Introduction: Students, especially at the senior high school level, are increasingly required to be able to develop according to predetermined standards. When the duration of learning increases, unconsciously, the duration of using the eyes also increases while the sleep duration decreases. Purpose: This study aims to analyze the correlation between short duration of sleep and decreased visual acuity among senior high school students. Methods: A cross-sectional study design was conducted, in which the students filled out questionnaires and underwent visual examination. The population was all final-year students at one of Sidoarjo Senior High School in East Java, with the age range of 16-18 years. Two variables involved in this study were sleep duration and visual acuity of the left and right eye. The data will be analyzed using Spearman Rho correlation analysis to determine the cause and effect of the two variables studied. Results: The sample according to the gender was 45.5% male and 54.5% female. The sample according to the age range was 76.1% in 17 years old and 23.9 % in 18 years old. The correlation test results were 0.277 and 0.009 for the correlation coefficient and the significance value for the right eye. The results were 0.234 for the correlation coefficient and 0.028 for the significance value for the left eye. There was a significant correlation between sleep duration and the visual acuity reduction. Conclusions: This study reveals that less sleep duration of the final year students between 16-18 years old range may be associated with reduced visual acuity among students.